APPLICATION OF STEM-BASED WORKSHEETS TO INCREASE INTEREST AND LEARNING OUTCOMES OF 5TH GRADE STUDENTS IN CHANGING STATES OF MATTER - Nadhifah, Nisa; Supriadi, Bambang; Handayani, Rif'ati Dina; Mariya, Mariya (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2022)
AbstractThis research aims to increase the interest and learning outcomes of 5th grade students at SDN Triwung Lor 2 by applying STEM-Based student worksheets on the material of changing state of matter. This research is a Classroom Action Research (CAR) conducted on 22 students of 5th grade at SDN Triwung Lor 2 Probolinggo City, consisting of 10 male and 12 female students. The data were collected through observation sheets, questionnaire sheets, pre-tests, and post-tests. The increase in student’s interest and learning outcomes was calculated by N-gain. The results showed that STEM-based worksheets could increase student’s interest and learning outcomes with the N-gain score on learning interest of cycle I and cycle II included with low criteria. While the learning outcomes experienced an insignificant increase because the learning outcomes in cycle I were included in the moderate criteria and cycle II were included in the low criteria. This research concludes that the application of STEM-based worksheets can increase student’s interest and learning outcomes.Keywords: Student Worksheets; Learning Interest; Learning Outcomes